THE ROLE OF MONETARY INSTRUMENTS IN ECONOMIC EMERGENCIES. STUDIES OF RUSSIAN ECONOMISTS OF THE EARLY XX CENTUR - I. Nazarova (Вестник университета)
The relationship of such key macroeconomic concepts as the monetary system and the national economy in extreme economic situations (in the “military economy”) has been di sclosed. During the process of analyzing the works of Russian scientists of the early twentieth century, the specifics of the monetary instruments of market regulation in the conditions of the “military economy” and the change in the structure of the monetary mass have been considered. It has been shown, that the classical forms of credit (military loans, taxes), due to their low efficiency, give way to credit money, which during the demonetization of gold, play the role of a financial resource (“bills of exchange for the future”).